Estimação do Value at Risk via enfoque bayesiano - Marques, Felipe Tumenas (Universidade Federal de São Carlos, 2007)
The continuous development of new financial instruments brings more and more investment options for market participants. These investment options also bring a bigger necessity to evaluate the risk embedded in these new financial instruments. Risk Analysis can be defined as an attempt to measure the uncertainty degree in the attainment of the expected return in a financial application and the standard measure to evaluate financial risk is the Value at Risk. This work aims to develop a new approach to estimate the Value at Risk, considering both the market data and the specialists´ opinion.
Value at Risk Estimation by a Bayesian Approach
Keywords: Análise de risco; Inferência bayesiana.; Value at Risk; Market risk; Bayesian inference; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA